Kontradyktoryjność vs. inkwizycyjność w procesie karnym – spór polityczny czy naukowy? - Górnicka, Maria (2019)
The author of the article presents a political and a scientific dispute between adversarial system and inquisitorial system. The aim of the study is to show that disputes are severe, conducted on various levels and in different ways. These disputes are difficult to categorically separate
Keywords: kontradyktoryjność; inkwizycyjność; doktryny polityczne; postępowanie karne